Psychiatric and neuropsychological manifestations of sistemic lupuserythematosus - Fietta, P.; Fietta, P.; Delsante, G. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which may involve any organ and system, including peripheral, autonomic, and central nervous system (CNS). According to the American College of Rheumatology nomenclature, the term “neuropsychiatric SLE” identifies neurological and psychiatric syndromes occurring in patients at any time, not attributable to other causes, and categorized in three main groups, namely neurological syndromes of CNS, neurological syndromes of peripheral nervous system, and diffuse psychiatric/neuropsychological syndromes. The SLE neurological and psychiatric manifestations are usually reported together, and specific data on SLE psychopathology are limited. We aimed to electively focus on prevalence, pathogenesis, diagnostic aspects, and current therapeutic options of diffuse psychiatric/neuropsychological SLE syndromes in adult and pediatric patients. Methods: A detailed search of concerning literature was performed in PubMed (U.S. National Library of Medicine) database. Results: In both adulthood and childhood, psychiatric/neuropsychological syndromes are frequent and challenging SLE manifestations, whose prevalence is likely underestimated, owing to systematic assessment is not routinely performed in patients. Ischemia (due to disease-related vascular injury or cerebral vasospasm) and inflammatory/immunopathologic mechanisms appear to be the main pathogenic factors. Standardized treatment guidelines are not presently available, however, therapeutic recommendations have been proposed. Conclusions: Due to the high prevalence and significant suicidality risk of SLE psychiatric syndromes, systematic assessment to provide prompt diagnosis and adequate care should be critical part of SLE patients’ evaluation protocol, and universally accepted and validated evaluating tools should be performed and introduced in the clinical practice, as well as widely experienced therapeutic strategies.